1976
DOI: 10.1111/j.1365-2141.1976.tb03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization, Partial Purification and Radioassay for the Intrinsic Factor Receptor from the Ileal Mucosa

Abstract: A macromolecule which binds intrinsic factor saturated with vitamin B12 has been solubilized from the guinea-pig ileum by homogenization followed by mechanical disruption without organic solvents or detergents. This intrinsic factor 'receptor' was further purified by precipitation with 30% saturated ammonium sulphate, centrifugation at 105000 g, and filtration through Sephadex G-200. Failure to precipitate the receptor following centrifugation at 105000 g for 3 h and filtration of the receptor with the include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…IN VITRO STUDIES Cobalamin is absorbed in the ileum (17,30), and Herbert (77) suggested that the absorption of cbl was by means of specialized receptors for IF-cbl complex in the ileum. The presence of ileal binding and presumed receptors has been confirmed from various animal species (38,39,70,108). In humans, binding is present over the entire ileum second half of the small intestine.…”
Section: Mucosal Phasementioning
confidence: 87%
“…IN VITRO STUDIES Cobalamin is absorbed in the ileum (17,30), and Herbert (77) suggested that the absorption of cbl was by means of specialized receptors for IF-cbl complex in the ileum. The presence of ileal binding and presumed receptors has been confirmed from various animal species (38,39,70,108). In humans, binding is present over the entire ileum second half of the small intestine.…”
Section: Mucosal Phasementioning
confidence: 87%
“…Cubilin was iodinated (ϳ10 6 Bq/g) by the iodogen method (Pierce). The 125 I-labeled cubilin was purified by S-300 (Pharmacia) gel filtration, and 10 6 cpm was loaded on the megalin column.…”
Section: Methodsmentioning
confidence: 99%
“…However, early studies have indicated that both an intrinsic factor-B 12 -binding protein (6) and the target protein of teratogenic antibodies (41) could be released, at least in part, from intestinal or renal tissue using mechanical dissociation in the absence of detergents. We further showed that some cubilin was released by heparin, phosphorylethanol- amine, and EDTA, whereas the membrane association was resistant to acid conditions.…”
Section: Fig 4 the Extracellular Modules Of Cubilinmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the availability of Ca2+ is limited, Mg2+ can enhance Ca2+-dependent binding of IF-B-12 complex to its receptor (Beesley & Bacheller, 1980). A number of investigators have utilized mechanical shearing forces (Cotter & Rothenberg, 1976;Okuda & Fujii, 1977) and/or detergent solutions Vol. 200 (Katz & Cooper, 1974;Schneider et al, 1974;Marcoullis & Graisbeck, 1977) to solubilize the ileal IF-B-12-complex receptor from several species.…”
Section: Efficient Intestinal Absorption Of Vitaminmentioning
confidence: 99%